Nutritional analysis: food advertising during children's television programming in Nepal - Johnson, Ashlie N., author; Menger-Oglle, Andrew D., author; Morgan, John A., author; Graham, Dan J., author (Colorado State University. Libraries, 2017)
This study seeks to describe the TV food marketing landscape that children experience in the southeast Asian country of Nepal. We conducted a content analysis on 12 hours of commercials, categorizing commercials based available food nutrition information. Results show that 55% of airtime commercials during children’s programming was dedicated to foods. Over 80% of the food commercials had excessive amounts of saturated fat, sugar or sodium; over half of the products that containing excess sugar. Results from this study suggest that the media landscape in Nepal isn’t meeting WHO recommendations for advertising foods to children.
147 - Ashlie Johnson
Keywords: nutrition; children's television; international